2001
DOI: 10.1080/02724980143000073
|View full text |Cite
|
Sign up to set email alerts
|

The implicit benefit of learning without errors

Abstract: Two studies examined whether the number of errors made in learning a motor skill, golf putting, differentially influences the adoption of a selective (explicit) or unselective (implicit) learning mode. Errorful learners were expected to adopt an explicit, hypothesis-testing strategy to correct errors during learning, thereby accruing a pool of verbalizable rules and exhibiting performance breakdown under dual-task conditions, characteristic of a selective mode of learning. Reducing errors during learning was p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
155
3
6

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(175 citation statements)
references
References 0 publications
11
155
3
6
Order By: Relevance
“…However, alternative explanations could provide a outcome and the desired goal (Rabbitt, 1966(Rabbitt, , 1967. In addition, they generate rules, 130 hypotheses and knowledge about future task requirements so as to improve subsequent 131 performance (Maxwell, Masters, Kerr, & Weedon, 2001). Therefore, an error trial leads to 132 greater cognitive effort due to the additional processing that takes place when compared to an 133 errorless trial (Lam et al, 2010).…”
mentioning
confidence: 99%
“…However, alternative explanations could provide a outcome and the desired goal (Rabbitt, 1966(Rabbitt, , 1967. In addition, they generate rules, 130 hypotheses and knowledge about future task requirements so as to improve subsequent 131 performance (Maxwell, Masters, Kerr, & Weedon, 2001). Therefore, an error trial leads to 132 greater cognitive effort due to the additional processing that takes place when compared to an 133 errorless trial (Lam et al, 2010).…”
mentioning
confidence: 99%
“…Low T3-Fz coherence is thought to reflect less dependence on explicit processes for motor performance (see Deeny, Hillman, Janelle, & Hatfield, 2003;Zhu, Poolton, Wilson, Maxwell, & Masters, 2011b). As such, expert marksmen displayed lower EEG T3-Fz coherence than less skilled shooters (Deeny et al, 2003) and novice golfers who used an implicit motor learning paradigm (Masters, 1992;Maxwell, Masters, Kerr, & Weedon, 2001) displayed lower EEG T3-Fz coherence than more explicit learners (Zhu et al, 2011b). In a recent study that modified the continuous 24 tracking task paradigm for laparoscopic surgical skills training, T3-Fz alpha power coherence was greater when participants were made aware of the repeated waveform pattern compared to when participants were not, suggesting that T3-Fz alpha power coherence reflects the use of explicit knowledge of characteristics of the pattern to support tracking performance (Zhu et al, 2011a).…”
mentioning
confidence: 99%
“…The errorless groups in both studies had significantly greater putting accuracy in the retention and transfer tests than the errorfull and random groups. Maxwell et al (2001) 24 also reported that when the retention tests were performed with a secondary task, there were further significant reductions in putting performance for the errorfull and random groups, but no significant changes for the errorless group. The secondary task used was tone counting and required the golfers to count the number of high but not low pitch sounds while putting.…”
Section: Errorless Versus Errorfull Practicementioning
confidence: 99%
“…Six motor learning studies (see Table 2) compared the learning effects of altering the structure of the golf practice session via massed versus distributed practice (Dail & Christina, 2004), block versus random practice (Goodwin & Meeuwsen, 1996;Guadagnoli, Holcomb, & Weber, 1999;Porter & Magill, 2010) as well as errorless versus errorfull practice (Lam, Maxwell, & Masters, 2010;Maxwell, Masters, Kerr, & Weedon, 2001). …”
Section: Structure Of Practicementioning
confidence: 99%
See 1 more Smart Citation